2011
DOI: 10.1007/s10725-011-9568-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salinity tolerance in sorghum (Sorghum bicolor L.) using ion accumulation, proline and peroxidase criteria

Abstract: Salt tolerance of sorghum varieties in terms of fresh weight, ion accumulations, proline content and peroxidase activity was analyzed in this study. Three sorghum varieties, Payam, Kimia, and Jambo, differing in salt tolerance, were grown in a greenhouse-hydroponic culture with a complete nutrition solution to which 0, 50, 100, 150 and 200 mM NaCl was added. Plant roots and leaves were harvested at 15 and 30 days after treatment and subjected to analysis. Clear decline in K ? and Ca 2? concentrations and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 63 publications
1
16
1
Order By: Relevance
“…At the VG stage, half of the genotypes had POD activity equal or below their control levels whereas at the RP stage, salinity increased POD activity of all genotypes. Some studies have indicated that ST is related to POD activity (Sairam et al, 2005;Bavei et al, 2011;Gao et al, 2013). Conversely, Fan et al (2014) reported higher POD activity in all salt tolerant and in one salt sensitive barley genotypes grown under salt stress, but they found no significant relationship between increased POD activity and ST.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At the VG stage, half of the genotypes had POD activity equal or below their control levels whereas at the RP stage, salinity increased POD activity of all genotypes. Some studies have indicated that ST is related to POD activity (Sairam et al, 2005;Bavei et al, 2011;Gao et al, 2013). Conversely, Fan et al (2014) reported higher POD activity in all salt tolerant and in one salt sensitive barley genotypes grown under salt stress, but they found no significant relationship between increased POD activity and ST.…”
Section: Discussionmentioning
confidence: 94%
“…Guaiacol peroxidase (POD) has been considered as a stress enzyme, since its regulation is dependent on biotic and abiotic stresses, and it serves as a protective tool against harsh environments (Bavei et al, 2011). Using guaiacol as a reductant, POD activates H 2 O 2 decomposition to produce H 2 O and O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As the physiochemical properties of Na + and K + are similar, uptake of K + is affected by high Na + levels (Hossain et al, 2011), which lead to reduced potassium and Ca 2+ uptake (Bavei et al, 2011;Tavakkoli et al, 2011). In the current study shoot and root K + and Ca 2+ contents were drastically reduced under salinity stress in both wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Preferential deposition of Na + ions in the shoot occurred in the leaf base (Lacerda et al 2003), and increasing levels of Ca 2+ in the culture solution enhanced growth and lowered sodium uptake of sorghum plants (Asghar et al 2009). It was also observed that the salt-tolerant genotype Jambo accumulated more Ca 2+ both in the leaf and root tissues than the sensitive varieties, Kimia and Payam (Bavei et al 2011b).…”
Section: Salt Stressmentioning
confidence: 91%